Relationship between bone mineral density and hyperuricemia in obesity: A cross-sectional study - Zhang, Yi; Tan, Min; Liu, Boyu; Zeng, Manxia; Zhou, You; Zhang, Mengru; Wang, Yikai; Wu, Jing; Wang, Min (Frontiers in Endocrinology, 2023)
Background: Obesity is an increasingly severe global public health issue. This study aims to estimate the cross-sectional association between bone mineral density (BMD) and hyperuricemia (HU) in obesity. Method: A total of 275 obesity subjects (126 males and 149 females) participated in this cross-sectional study. The obesity was diagnosed as body mass index (BMI) ≥ 28kg/m2, whereas HU was defined as the blood uric acid level of 416umol/L in males and 360umol/ L in females, respectively. The BMD of the lumbar spine and right hip was measured by DXA dual-energy X-ray absorptiometry. The multivariable logistic regressions were employed to examine the relationship between BMD and HU in obesity, with the adjustment of gender, age, fasting blood glucose, fasting insulin, HOMA-IR, cholesterol, triglycerides, low-density lipoprotein, high-density lipoprotein, creatinine, blood urea nitrogen, hsCRP, cigarette smoking and alcohol drinking status. Result: The overall prevalence of HU was 66.9% in this obesity population. The mean age and BMI of this populations is 27.9±9.9 and 35.2±5.2. The multi-variable adjusted OR (the highest vs lowest BMD quartile) demonstrated a negative relationship between BMD and HU in total (OR=0.415, 95%CI: 0.182-0.946; P=0.036), L1 (OR=0.305, 95%CI: 0.127-0.730; P=0.008), L2 (OR=0.405, 95%CI: 0.177-0.925; P=0.032) and L3 (OR=0.368, 95%CI: 0.159-0.851; P=0.020) lumber, respectively. In subgroup analysis for male population, the BMD was also negatively associated with HU in total (OR=0.077, 95%CI: 0.014-0.427; P=0.003), L1 (OR=0.019, 95%CI: 0.002-0.206; P=0.001), L2 (OR=0.161, 95%CI: 0.034-0.767; P=0.022), L3 (OR=0.186, 95%CI: 0.041-0.858; P=0.031) and L4 (OR=0.231, 95%CI: 0.056-0.948; P=0.042) lumber, respectively. However, such findings were not existed in females. In addition, there was no significant relationship between hip BMD and HU in obesity. Conclusion: Our results showed that the lumber BMD was negatively associated with HU in obesity. However, such findings only existed in males, rather than females. In addition, no significant relationship between hip BMD and HU existed in obesity. Due to the limited sample size and nature of cross-sectional design, further large prospective studies are still needed to clarify the issues.